2018
DOI: 10.3390/healthcare6020069
|View full text |Cite
|
Sign up to set email alerts
|

A Community Study of Borrelia burgdorferi Antibodies among Individuals with Prior Lyme Disease in Endemic Areas

Abstract: The objective was to examine the prevalence of Borrelia antibodies among symptomatic individuals with recent and past Lyme disease in endemic communities using standard assays and novel assays employing next-generation antigenic substrates. Single- and two-tiered algorithms included different anti-Borrelia ELISAs and immunoblots. Antibody prevalence was examined in sera from 32 individuals with recent erythema migrans (EM), 335 individuals with persistent symptoms following treatment for Lyme disease (PTLS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It is possible that there was variation in the level of autoantibodies based on the Bb serostatus of the individuals within the LD case groups. We examined the distribution of antineuronal autoantibodies and serum activation of CaMKII activity in cases testing negative vs positive for Bb antibodies using two classification methods - the single tier C6 ELISA (C6 ELISA) and the more specific two-tier algorithm (C6 ELISA and EUROLINE –RN-AT IgG) as described previously ( Strobino et al., 2018 ). Bb serostatus at the time of sample collection was not associated with significant differences in autoantibodies or CaM kinase activation, regardless of whether serostatus was categorized based on the C6 ELISA alone or the two-tier algorithm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that there was variation in the level of autoantibodies based on the Bb serostatus of the individuals within the LD case groups. We examined the distribution of antineuronal autoantibodies and serum activation of CaMKII activity in cases testing negative vs positive for Bb antibodies using two classification methods - the single tier C6 ELISA (C6 ELISA) and the more specific two-tier algorithm (C6 ELISA and EUROLINE –RN-AT IgG) as described previously ( Strobino et al., 2018 ). Bb serostatus at the time of sample collection was not associated with significant differences in autoantibodies or CaM kinase activation, regardless of whether serostatus was categorized based on the C6 ELISA alone or the two-tier algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Stored serum samples from a community serosurvey conducted in hyperendemic LD areas of New York, New Jersey, and Connecticut were examined; the NYS Psychiatric Institute IRB approved the study sample collection and all participants signed informed consent ( Strobino et al., 2018 ). Clinical details of LD history were obtained through questionnaires at the time of the survey and through follow-up telephone contact to obtain additional information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2018 publication by Strobino et al61 indicated that for convalescent EM, combinations of the C6 ELISA with a second-tier ELISA or line blot may provide useful alternatives to WB-based testing algorithms, but this needs to be confirmed in larger clinical studies. For those without an EM rash (and not meeting the definition of PTLDS), the two-tiered testing strategy for diagnosing B. burgdorferi misses a large proportion of cases,62 and this approach cannot diagnose new species of Borrelia, including B. miyamotoi and B. burgdorferi sensu lato , which are also known to cause chronic illness 63,64.…”
Section: Discussionmentioning
confidence: 99%
“…Seroconversion was also rare in samples from the Lyme Disease Biobank, where only 3 of 83 samples (3.6%) from patients with EM > 5 cm seroconverted at the convalescent draw (2-3 months after the acute draw) (23). Other widely known limitations of serological tests are that they are unable to distinguish between a prior exposure to Bb and an active infection, may crossreact with non-Bb antibodies, are subject to variable results depending the selection of antigens used in the first-tier test (31) and some assays, especially the Western immunoblot, require interpretation that may introduce bias (32,33).…”
Section: Serological Testingmentioning
confidence: 99%